2006
DOI: 10.1063/1.2345225
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dark line defects induced by catastrophic optical damage in broad-area AlGaInP laser diodes

Abstract: The authors present a detailed investigation of defects generated during catastrophic optical damage (COD) in high-power 650nm AlGaInP lasers using microphotoluminescence (μ-PL) mapping, focused ion beam (FIB) microscopy, and deep-etching techniques. High-resolution μ-PL images demonstrated that during COD, nonradiative dark line defects (DLDs) originate from the front mirror of the laser and propagate in several branches into the laser perpendicular to the output facet. Furthermore, FIB microscopy identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…either as panchromatic maps or at the QW emission wavelength. COD generates areas of substantially reduced QW emission in such maps, the so-called dark bands [85,[87][88][89][90][91][92][93][94][95][96][97]. The barriers, into which the QW is physically embedded, are typically less or even not affected by this type of damage.…”
Section: Failure Analysis Of Devices Affected By Codmentioning
confidence: 99%
See 1 more Smart Citation
“…either as panchromatic maps or at the QW emission wavelength. COD generates areas of substantially reduced QW emission in such maps, the so-called dark bands [85,[87][88][89][90][91][92][93][94][95][96][97]. The barriers, into which the QW is physically embedded, are typically less or even not affected by this type of damage.…”
Section: Failure Analysis Of Devices Affected By Codmentioning
confidence: 99%
“…The crystallographic structure of the dark bands is described as polycrystalline [90,93]. This suggests that they originate from a re-crystallization process.…”
Section: Failure Analysis Of Devices Affected By Codmentioning
confidence: 99%
“…Catastrophic optical mirror damage has been extensively investigated, but very limited reports on bulk damage in broad-area lasers have been presented. Several groups investigated failure modes in broad-area lasers in recent years [13][14][15] and our group recently reported a reliability and failure mode investigation of broad-area lasers using electron beam induced current (EBIC) and high-resolution transmission electron microscope (HR-TEM) techniques [16,17]. In the present study, we report on our investigation of catastrophic facet and bulk degraded broad-area InGaAs strained QW single emitters using various analytical techniques including EBIC, focused ion beam (FIB), and HR-TEM.…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed by electron beam induced current, real-time electroluminescence, and transmission electron microscopy analysis that the active region of the COD failed lasers reveals an extensive layer intermixing and a highly defective core of molten and resolidified material [5,6]. Therefore, investigating the defects in GaAs crystal and LDs is important to improve the performance of the LDs [7,8]. Another mechanism leading to COD is identified that the spatial hole burning effect causes the near-field intensity distributing periodically, such distribution results in an extra enhancement of the facet heating, and the COD occurring finally [9].…”
mentioning
confidence: 92%